The Impact of Ongoing Israel-Palestine War on China National Interest: Between Benefit and Expectation - Huswatun Miswar, Syarifah (UI Scholars Hub, 2024)
War is not always bad, for certain parties war can sometimes be a source of grace that can be functioned, for example in the case of the Israeli-Palestinian war. This article aims to find out how the ongoing war has a positive impact on China and how China's involvement in the ongoing Palestinian-Israeli peace efforts have cost more than 25,000 lives. This study uses a qualitative analysis method, where the latest and relevant facts and information related to the Israeli-Palestinian war and China's attitude towards the ongoing war are collected, then analyzed based on the framework of the topic being discussed, namely seeing the war from the Chinese perspective. The results of this study conclude that the ongoing war between Israel and Palestine indirectly benefits China both geo-economically and geopolitically and even strategically. The war not only reduces American dominance in the Asian region politically and economically, the war also gives China the opportunity to strengthen China’s soft power in the Middle East and Africa with its involvement as a mediator.